The effect of plant-based nitrites and natural antioxidants on the oxidative stability of meat products - Aleksandra Silovska Nikolova; Daniela Belichovska (Institute of Knowledge Management, 2023)
: Nitrites are additives that belong in the group of preservatives. They prevent the growth and development of microorganisms. Seen from a technological point of view, they are important for the development and stability of color in meat products, they prevent the lipid oxidation, and they create meat products with excellent taste. Due to their multipurpose, they are among the most used additives in the meat processing industry. The lipid oxidation, and the development of an off- flavor negatively affect the quality of meat products, thus decreasing their shelf life. The use of nitrites has a negative effect on the consumers’ health. The demand for natural meat products has increased significantly during the last decades. It is very difficult and quite complex to eliminate or replace nitrites in meat processing. This topic has been worked on for more than six decades. Numerous research has determined that one substance cannot be found as an alternative substitute for them and their effects. The natural source of plant-based nitrites that contain a higher percentage of nitrates in combination with starter cultures, as well as additional antioxidants, can contribute to the prevention of oxidative processes in meat products.
Keywords: nitrites, antioxidants, oxidation, contribution, meat products